PENGEMBANGAN PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN M-APOS PADA MATERI TURUNAN FUNGSI ALJABAR DI SMA - Sari, Winda Widya; Halini, Halini; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine and describe the feasibility of a mathematics learning design with the M-APOS approach on the subject derivative of algebraic functions in high school. The feasibility of the learning design was seen from the aspect of validity and practicality. The research method used was the Research and Development (R&D) method. The development model used in this study refered to the ASSURE development model which consists of five stages, including analysis of student characteristics, formulating learning objectives, selecting methods, media, and teaching materials, using media and teaching materials, and evaluation and revision. The learning design developed included RPP and LKPD following the M-APOS approach which includ LKT, LKD, and Exercises. The results of the study, including the mean score of validity, was 4 and the opinions of the validators and students who said that the learning design was practical or easy to apply in learning. So, the mathematics learning design with the M-APOS approach on the derivative material of algebraic functions in high school was feasible with valid and practical criteria for use.Â Keywords: Derivative of Algebraic Functions, Learning Design, M-APOS Approach